Onboard intelligent flight control in a particular situation - Казак, В.М.; Шевчук, Д.О.; Яковицька, О.Ю. (Proceedings of National Aviation University (archive), 2008)
Now new aviation tactics designing presumes development and application of the onboard intellectual control systems working in extra situation appeared in flight in a real-time mode for aircraft controllability provided. The principle of functioning onboard intellectual control systems based on logic–linguistic models and neural networks are considered in the article. The developed mathematical model of the task formation optimum variant flight in extra conditions is presented.